Biological basis for human capacitation—revisited - De Jonge, Christopher (Human reproduction update, 2017)
A little more than a decade ago a review entitled 'Biological basis for human capacitation' was published. A primary conclusion of the review was that with all the technological advances that have been made since the first experiments demonstrated the in vivo requirement of capacitation for fertilization, very little progress had since been made, most significantly for human. The present review was carried out to provide an update on the biological basis for human capacitation. It briefly revisits the original schema, presents a review of the literature that urged research interest in human sperm capacitation and puts under the spotlight the original definition of capacitation balanced against the limitations of experiments in vitro to characterize a complex process that necessarily mandates a female component, and very recent findings in the mouse. It also includes proposed considerations for new thinking regarding capacitation, and progress toward understanding the biology of human capacitation. The PubMed, Google Scholar and Scopus literature databases were reviewed extensively using inclusive, broad and multispecies search terms without publication date limitation. Comprehensive screening of the literature database showed that no papers regarding human sperm capacitation in vivo have been published in the past 20 years. Recent experiments in the mouse have provided compelling and unanticipated data regarding capacitation and in vivo fertilization. Questions were posed and addressed regarding: stimuli for initiation of capacitation, capacitation relative to the cumulus-oocyte complex, comparison between in vivo and in vitro capacitation, and potential species-specific differences in location and timing of capacitation. There has been no progress on the in vivo biology of human sperm capacitation since before the turn of the century. Human IVF and its technologies may likely have inhibited, and continue to hold back, any future in vivo experiments that would address one or more questions regarding acquisition of fertilizing capacity in human. The limiting factor for progress in the area is access to funding and human subjects.